The effect of a suggested exercise program for the development of an element Fitness in the study of theatrical fitness I have Performing arts students / College of Arts the total (Journal of the College of Basic Education, 2023)
Rehearsals are one of the main components of a theatrical fitness lesson and have multiple purposes.The exercises work on developing many of the students' motor abilities, such as agility, flexibility, and strength.and speed. Agility is one of the important physical capabilities necessary in our daily lives, and the actor needs it. Especially as his need for flexibility and balance.And by agility, we mean “the individual’s ability to meet quickly and control precise movements while savingIn the effort and the ability to jump or jump with